Can the Interdisciplinarity of Cognitive Science Be Saved Through Deconstruction? - Nowakowski, Przemysław R. (Studia Philosophiae Christianae, 2022)
This paper discusses the resources for deconstruction offered by cognitive science, drawing inspiration from David Gunkel’s work on the topic (Deconstruction, MIT Press 2021). The gesture of deconstruction is seen as having a positive impact on the development of this interdisciplinary field by challenging misleading dichotomies and examining its underlying assumptions, such as the symmetry of integration. ------------------------- Received: 6/11/2022. Reviewed: 13/12/2022. Accepted: 20/12/2022.